Experimental Study on Single-excavation Compound Shock-reflection Blasting Technology of Protective Layer - MA Mengmeng; ZHENG Jiawei; DU Haoliang; ZHAO Zhenfu; LU Wenbo (Renmin Zhujiang)
The excavation of the protective layer of the dam foundation needs to balance the excavation quality and high construction speed. Based on the excavation of the diversion channel foundation protection layer of the DBDP Hydropower Station in Pakistan, this paper proposes a compound shock-reflection blasting technique featuring a hollow iron ball installed at the gun hole's bottom and energy dissipation materials. The energy control principle of this technology is analyzed by theoretical analysis and numerical simulation, and the technological feasibility and the influence of blasting parameters are studied by field tests. The results show that the compound shock-reflection blasting technique realizes the control and utilization of the explosion energy through multiple reflections of the explosion shock wave on different interfaces. Compared with the conventional cushion blasting hole method, the energy dissipation capacity at the hole bottom is increased by 20%, and the energy concentration between holes is increased by 18.5%, effectively mitigating the damage to the rock mass at the bottom. Under field test conditions, the excavation molding effect of the compound shock-reflection blasting technique is close to that of the traditional layered excavation method, but the construction speed can be increased by 3~4 times. At the same time, the excavation shaping effect can be significantly improved by appropriately reducing the row distance between the holes.